(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Many,individuals experience various types of heightened awareness and may seem overly sensitive. These sensitivities may be to physical senses such as sight,sound, smell, movement and touch. For example, they may be extremelyuncomfortable when they have a wrinkle in their sock, or unable to concentrate because of the sound of a clock ticking on the other side of the room.Sensitivities of the , are often to mental and emotional over-awareness. Forexample, picking up on the of someone close to them, having extreme sensitivity to their own internal emotions, and taking in external information at a significantly higher rate than those around them.